Analisis Perubahan Budaya Sekolah Melalui Peresmian Perpustakaan Ramah Anak untuk Meningkatkan Literasi Siswa Sekolah Dasar - Muhammad Naufal Zulkarnain Nafis; Nilna Silfara Zukhriya; Laura mar'atus M.R; Shobihatul Fitroh Noviyanti (Al-Kindi, 2026)
This study aims to analyze changes in school culture through the inauguration of a child-friendly library in improving the literacy of elementary school students. The background of the research is based on students' low reading interest and the underutilization of the school library. The novelty of this study lies in its focus on the relationship between a child-friendly library and shifts in school culture. Using a qualitative descriptive method, data were gathered through observation, interviews, and documentation involving the principal, teachers, and students. The results indicate that the child-friendly library positively influences school culture, as evidenced by improved reading habits, a comfortable learning environment, and increased student participation in literacy activities. Furthermore, this facility encourages teachers to actively utilize literacy resources in the learning process. Consequently, the presence of a child-friendly library serves as an effective effort to build and strengthen a literacy culture within the school environment.